Manipulation of carbohydrate availability to promote training adaptations in endurance trained individuals - Salokannel, Meri (2018)
Training with low CHO availability has been shown to improve fat oxidation which is important for endurance performance by sparing glycogen. Therefore, the aim was to investigate whether performing high intensity interval training (HIIT) in the evening, followed by overnight fast and commencing low intensity training (LIT) in the following morning with low CHO availability will enhance training adaptations. First, pilot study was delivered to explore the acute effect of this strategy on fat oxidation. Training intervention was then delivered to investigate the effect of this strategy on endurance training adaptations. Subjects were endurance trained healthy males and females. Six subjects took part in the pilot study, which was delivered in crossover design. In that all subjects performed two HIIT-LIT combinations with staying either fasted after HIIT until finishing LIT or consumed food after HIIT and before LIT. Altogether 17 subjects completed training intervention, which included four-week training period, where HIIT-LIT training combination was performed twice a week. Subjects were divided into two groups: FASTED (stayed fasted after HIIT until finishing LIT) and FED (consumed food after HIIT and before LIT). Pre- and post-testing included VO2max test, anaerobic test, 60 min submaximal test to evaluate substrate oxidation and venous blood samples were taken. In the pilot study fat oxidation was higher during LIT (p<0.05) after staying fasted than when consuming food after HIIT and before LIT. After the intervention VO2max increased significantly in both groups (FASTED: 4±1%, FED: 5±2%, p<0.05) with same magnitude, whereas maximal speed was greater only in the FASTED group (p<0.05). Change in lactate concentrations were significantly higher in the FASTED than FED group after the VO2max test (p<0.05). The running time in the anaerobic test was improved in the FASTED group, but not in FED (from 64.1±5.2 s to 86.3±5.2 s and from 56.4±5.4 to 66.9±7.5 s, respectively). Substrate oxidation did not change after training period in either of the groups. HR was lower during submaximal test in the FASTED group after the intervention (p<0.05), whereas no change was found in the FED group (p>0.05). In conclusion, training with periodised CHO availability around specific training sessions do not hinder training adaptations and enhances the capacity to perform high intensity exercise and may promote other adaptations. We could speculate that the enhanced capacity to perform high intensity exercise is due to elevated muscle glycogen stores and enhanced glycolytic enzymes, however future studies are needed to verify this.